Questioning Conventional Gender Roles in William Wycherley’s The Plain Dealer - Gurung, Golman (Interdisciplinary Journal of Management and Social Sciences, 2020)
This article argues that the notion of gender is not a fixed category and doesn’t have any given essence to it. The male and female characters in William Wycherley’s play The Plain Dealer perform roles that tend to challenge our traditional conception of gender roles. Gender identities are complex things and it is not possible to reduce them to simple and unproblematic essences. The Character Manly falls into the trap of a woman’s machinations and succumbs to her power. His lack of manliness and the Widow’s knowledge and alacrity prove that traditional gender roles are open to challenge and can be reversed by different characters in different situations. This article analyses the role of the characters in the light of Foucauldian discourse and Judith Butler’s theory of gender as performance.